Morphological Responses of Moringa (Moringa stenopetala L.) Accessions Seedlings to Irrigation interval under Greenhouse Conditions - Galgaye, Gebre Garmame; Beshir, Hussein Mohammed; Roro, Amsalu Gobena (Journal of Science and Development, 2021)
Moringa (Moringa stenopetala L.) has a wide range of adaptability and various uses for human life. However, the plant is not well researched under Ethiopian conditions to maximize its benefit and exploit its potential. Therefore, a pot experiment was conducted to investigate the morphological responses of M. stenopetala accessions seedlings to irrigation intervals under greenhouse conditions at Hawassa, Ethiopia. The experiment was conducted using three accessions (Konso, Arbaminch Zuria, and Humbo) and four irrigation intervals (daily, 5 days interval, 10 days interval, and 15 days interval watering) assigned in a completely randomized design with three replications. The accessions significantly differed for most of the morphological traits studied in this experiment. The accession Arbaminch Zuria was higher in seedling height, stem diameter, leaf area, root length, root fresh weight, root dry weight, total seedling fresh weight, and total seedling dry weight than the other accessions. There were no significant differences between Arbaminch Zuria and Konso accessions in leaf number and root diameter. Regarding the irrigation interval, the highest seedling height, stem diameter, leaf area, leaf number, root length, root diameter, root fresh weight, root dry weight, total seedling fresh weight and total seedling dry weight were obtained from the daily watering interval. In contrast, the lowest growth parameters were from the 15 days interval watering. The 10 and 15 days interval watering were statistically similar for seedling height and leaf number. Additionally, fresh and dry leaf weights were significantly influenced by the interaction effect of accession and irrigation interval. The Arbaminch Zuria accession grown under daily watering had the highest fresh and dry leaf weights compared to the other accessions. Shorter interval of irrigation, if possible daily, is recommended to produce quality Moringa seedlings in a shorter period.